Confession and Memory in Early Modern English Literature Penitential Remains - Stegner, Paul D.; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
This is the first study to consider the relationship between private confessional rituals and memory across a range of early modern writers, including Edmund Spenser, Christopher Marlowe, William Shakespeare, and Robert Southwell.
Keywords: Poetry and Poetics; Early Modern/Renaissance Literature